Functional Characterization of the PAX8 p.Leu264Pro Variant Identified in a Patient with a Müllerian Duct Anomaly - Lin He; Liangzhe Li; Yuxiao Li; Yujun Sun; Zhi Zheng; Chunfang Chu; Lin Li (Genes, 2026)
Background/Objectives: Müllerian duct anomalies (MDAs) are congenital structural abnormalities of the female reproductive tract with heterogeneous and incompletely defined genetic contributions. PAX8 is a developmental transcription factor implicated in thyroid and urogenital development. This study assessed the functional consequences of a rare PAX8 variant identified by whole-exome sequencing (WES) in an MDA cohort, without presuming a causal relationship. Methods: WES was performed in 150 patients with MDAs. The PAX8 c.791T>C (p.Leu264Pro) variant was evaluated using computational predictions, cellular assays, and RNA sequencing in a 293FT transient-overexpression model. Results: The heterozygous p.Leu264Pro variant was identified in one patient with a complex septate uterine, cervical, and vaginal anomaly and was absent from 120 controls. Parental samples were unavailable. No statistically significant difference in construct-derived PAX8 mRNA abundance was detected between PAX8-WT and PAX8-L264P, and both proteins showed predominantly nuclear localization. In the direct PAX8-WT-versus-L264P RNA-seq comparison, 76 transcripts had nominal p values below 0.05, but none remained significant after Benjamini–Hochberg correction, and no gene met the prespecified differential-expression criteria. AK5, RCBTB2, and IFT88 were identified as candidate PAX8-responsive genes in this experimental system. Conclusions: No major functional difference was detected between PAX8-WT and L264P under the tested conditions; however, these findings do not establish functional equivalence or exclude smaller, tissue-specific, or developmental-stage-specific effects. The p.Leu264Pro variant remains a variant of uncertain significance with respect to MDAs, and the functional results were not used as benign evidence under ACMG/AMP criterion BS3.